Association of Prepregnancy Obesity versus Excessive Gestational Weight Gain with Adverse Neonatal Outcomes in the United States - McLaren, Rodney A., Jr.; Rastogi, Deepa; Rastogi, Shantanu (American Journal of Perinatology, 2025)
Prepregnancy obesity (PPO) and excessive gestational weight gain (eGWG) during pregnancy, both are associated with adverse neonatal outcomes. The objective of this study was to compare the independent associations of PPO and eGWG with adverse neonatal outcomes.This was a retrospective cohort study of singleton, live births in the United States in 2018 using National Vital Statistics System data. These were divided into four groups: 1) normal prepregnancy BMI and normal GWG, 2) normal prepregnancy BMI and eGWG, 3) prepregnancy BMI >30 kg/m2 (PPO) and normal GWG and 4) PPO and eGWG. The adverse neonatal outcomes, including preterm delivery, large for gestational age (LGA) infants, assisted neonatal ventilation, low 5-minute Apgar scores, neonatal intensive care unit (NICU) admissions, and surfactant use were studied. These outcomes were compared among groups using ANOVA and multivariable analyses.Of the 1,477,062 births included, 21.8, 41.6, 10.4, and 26.3% were in groups 1 to 4, respectively. With group 1 as the reference group after correcting for significant factors, groups 2 to 4 had a higher risk (adjusted odds ratio with 95% confidence interval), for preterm delivery of <37 weeks 1.17 (1.14–1.20), 1.05 (1.02–1.09), and 1.14 (1.11–1.18) and for LGA infants 2.38 (2.31–2.44), 2.37 (2.29–2.45), and 3.91 (3.80–4.02) in groups 2 to 4, respectively. Further, patients with PPO with and without eGWG also had increased risk of immediate assisted neonatal ventilation 1.07 (1.02–1.12) and 1.16 (1.12–1.22), for 5-minute Apgar score <3 1.40 (1.19–1.65) and 1.38 (1.20–1.58), and for NICU admission in 1.04, (1.01–1.08) and 1.12 (1.09–1.15) for groups 3 and 4, respectively.Both PPO and eGWG were independently associated with preterm delivery and LGA infants. PPO with or without excessive GWG was also associated with low Apgar scores, more NICU admissions, and a higher need for immediate ventilatory support. This data supports the importance of prepregnancy weight loss to prevent or decrease adverse neonatal outcomes.
Keywords: prepregnancy obesity; gestational weight gain; prematurity; neonatal outcomes